SAT0260 PENTOXYFILLINE GEL FOR ORAL ULCERS IN PATIENTS WITH BEHÇET'S SYNDROME. (2nd June 2020) - Hatemi, G.; Yurttas, B.; Kutlubay, Z.; Cote, T.; Derkunt, Ş. B.; Yazici, Y.; Yazici, H.
Abstract : Background: Oral ulcers, the hallmark lesion of Behçet's syndrome (BS) can be disabling and impair eating, drinking and speaking. Despite recent advances in systemic medications for the treatment of oral ulcers, some patients do not achieve complete remission. Topical agents may help such patients by decreasing the pain and duration of oral ulcers. Pentoxyfilline (PTX) is a methylxanthine derivative that inhibits phosphodiesterase and is thought to have immunomodulatory effects in addition to improving blood flow which is its main reason for use in peripheral vascular disorders. Objectives: The aim of this study is to assess the efficacy and safety of PTX gel for oral ulcers in patients with BS. We also aimed to explore the best tools for the assessment of treatment response to topical agents in randomized controlled trials (Clinicaltrial.gov ID: NCT 03888846). Methods: This was an open-label, randomized, parallel group study comparing PTX gel in addition to colchicine (PTX-COL) with colchicine alone (COL). Patients with BS who were treated with colchicine and not using any other systemic medications for BS, having at least one oral ulcer that appeared during the last 48 hours were included. PTX 5% gel with a dose of 1000 mg/day was applied in 4 divided doses per day for 14 days. Patients were contacted daily for 14 consecutive days. Photographs were taken every 24 - 48 hours and graphical processing software was used to calculate the area of the index ulcer. Duration of the index ulcer, time to start of index ulcer shrinkage, time to 50% reduction in oral ulcer pain on a 10 mm visual analog scale (VAS), change from baseline in the area of the index ulcer over time, total number of oral ulcers and adverse events were evaluated. Results: A total of 41 patients were randomized, 39 patients (18 in the PTX-COL group and 21 in the COL group) completed the study and 2 patients in PTX-COL group withdrew from the study due to unacceptable dysgeusia and nausea. Mean duration of index ulcer, time to start of index ulcer shrinkage, time to 50% reduction in oral ulcer pain, and number of patients with no detectable ulcers on day 4 in each group were lower in the PTX-COL group as presented in the Table. Change from baseline in the area of index ulcer and pain score over time is shown in the Figure. There were no serious adverse events. Fifteen (75%) patients reported nausea, 11 (55%) reported dysgeusia and 2 reported vomitting in the PTX-COL group, while 2 patients (10%) reported nausea in the COL group. Conclusion: This pilot phase 2 open label, randomized controlled study supports the hypothesis that topical PTX in addition to colchicine accelerates the healing of BS oral ulcers compared to colchicine alone. A phase 3 controlled study with a higher number of patients is planned with improving the taste for tolerability of the product. Disclosure of Interests: Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker, Berna Yurttas: None declared, Zekayi Kutlubay: None declared, Tim Cote Employee of: Silk Road Therapeutics is in Washington, DC, USA, Şemsi Burak Derkunt Employee of: Silk Road Therapeutics is in Washington, DC, USA, Yusuf Yazici: None declared, Hasan Yazici: None declared